The Impact Of Electronic Marketing On Improving The Quality Of Electronic Banking Service In Commercial Banks In The Hashemite Kingdom Of Jordan (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The study aimed to identify the effect of electronic marketing on improving the quality of electronic banking services in commercial banks in Jordan from the point of view of their employees.The researcher adopted the descriptive approach, and the study sample consisted of (202) employees in commercial banks in Jordan, and to achieve the objectives of the study, the researcher developed a questionnaire that included eight dimensions and the study data were analyzed.The study reached a set of results that the total mean of the study’s dimensions reached (3.96) with a high degree. The results also showed that the quality of banking service in Jordanian commercial banks came at a high level according to the responses of the sample members. The results indicate that there is a statistical correlation between e-marketing and improving the quality of banking service in commercial banks in Jordan.